Bishop John Vitez and Early Renaissance Central Europe : The Humanist Kingmaker. - Matić, Tomislav (Amsterdam : Arc Humanities Press, 2022)
The first biography of John Vitez, an influential figure of the Early Renaissance, presenting a complex picture of cultural, political, and religious developments in Central Europe.
Description based on publisher supplied metadata and other sources.
Electronic reproduction. Ann Arbor, Michigan : ProQuest Ebook Central, 2023. Available via World Wide Web. Access may be limited to ProQuest Ebook Central affiliated libraries.
Keywords: Electronic books